A High-Resolution Melting Analysis with an Unlabeled Probe for CRISPR/Cas9-Induced ZBED6 Knockout Pigs Detection. (9th December 2020) - Liu, Xiaofei; Qiu, Songyin; Mei, Lin; Jing, Hongli; Lin, Xiangmei; Wang, Qin
Abstract: Background: The zinc finger BED-type containing six knockout (ZBED6-KO) pigs were created to improve economic traits by increasing the expression of insulin-like growth factor 2. They were generated by CRISPR/CRISPR-associated protein 9 (Cas9) technology and a single-base deletion of ZBED6 was found. An efficient and rapid method was needed to detect this type of pig. Objective: This study aimed to develop a high-resolution melting (HRM) method to detect ZBED6-KO pigs. Methods: An unlabeled probe and two primers were designed to develop the HRM method. The limit of detection, specificity, and accuracy of the established method were tested by the constructed plasmid and DNA extracts of tissue specimens. Results: The limit of detection by the established method was 10 2 copies/µL. The HRM method with an unlabeled probe showed good specificity and high accuracy. Conclusions: The established HRM analysis with an unlabeled probe showed it to be a highly effective, rapid, and reliable method to distinguish ZBED6-KO pigs from wild-type pigs. Highlights: It is the first time that HRM analysis with an unlabeled probe has been used in the detection of genome editing pigs by the CRISPR/Cas9 technology.